Identification of plasma lipid metabolism and potential biomarkers in patients with different coronary occlusive acute myocardial infarction - Chen, Hao; Zhang, Qingyi; Zhou, Ai; Zhang, Li; Li, Xing (Frontiers in Cell and Developmental Biology, 2025)
Acute myocardial infarction (AMI) is the main cause of death worldwide. We aim to compare the differences in plasma lipid metabolites between AMI patients and normal controls to search for biomarker molecules for AMI with different infarct sites. We enrolled 12 patients in Group A (left coronary artery occlusion), 15 in Group B (right coronary artery occlusion), and 14 in Group C (normal controls) from June 2020 to June 2021. Non-targeted lipidomic analysis was performed and a total of 93 differential lipid molecules were identified. Diagnostic efficiency was evaluated by receiver operating curve. Compared with Group C, there were nine lipid molecules with AUC>0.8 in Groups A and B. Compared with Group B, Group A had six lipid molecules with AUC>0.8. These lipid molecules belonged to the LPC, PC, TG, and DG classes. We focused on LPC (20:4) as a biomarker in AMI.